Clinical outcomes, local–regional control and the role for metastasis-directed therapies in stage III non-small cell lung cancers treated with chemoradiation and durvalumab. (August 2020) - Offin, Michael; Shaverdian, Narek; Rimner, Andreas; Lobaugh, Stephanie; Shepherd, Annemarie F.; Simone, Charles B.; Gelblum, Daphna Y.; Wu, Abraham J.; Lee, Nancy; Kris, Mark G.; Rudin, Charles M.; Zhang, Zhigang; et al.
Highlights: Disease control and toxicity outcomes with concurrent chemoradiation (cCRT) and durvalumab in clinical practice appear consistent with the outcomes described in the PACIFIC trial. Patients treated with cCRT and durvalumab appear to have improved local–regional control compared to historical data of patients treated with cCRT alone. Nearly half of patients appear to have oligometastatic disease at first progression and may be candidates for metastasis-directed therapies. Abstract: Background and purpose: Concurrent chemoradiation (cCRT) and durvalumab is standard therapy for patients with unresectable stage III non-small-cell lung cancers (NSCLC). Data is limited on outcomes with this regimen outside of clinical trials. Local-regional control rates remain undefined. Materials and methods: We reviewed patients with stage III unresectable NSCLCs treated between November 2017 and February 2019 with cCRT and ≥1 dose of durvalumab. We examined 12-month progression-free-survival (PFS), overall-survival (OS), toxicities, and the incidence and pattern of local–regional and metastatic failures. Results: Sixty-two patients (median follow-up 12 months) with median age of 66 years of which 73% had stage IIIB ( n = 33) or IIIC ( n = 12) disease started durvalumab a median of 1.5 months from the end of cCRT and were treated with a median of 8 months of durvalumab. Common reasons for stopping durvalumab included disease progression (32%, 20/62) and toxicity (24%, 15/62). The estimated 12-month PFS and OS were 65% (95% CI: 51–79%) and 85% (95% CI: 75–95%), respectively. The cumulative 12-month incidence of local–regional and distant failures were 18% (95% CI: 5.9–30%) and 30% (95% CI: 16.3–44.5%), respectively. Among patients with distant metastatic disease ( n = 17), 47% had oligometastatic disease. High tumor mutation burden (≥8.8 mt/Mb) or PD-L1 (≥1% or PD-L1 ≥ 50%) did not predict improved PFS. Conclusions: Outcomes with cCRT and durvalumab in practice align with the PACIFIC trial. A substantial minority of patients are candidates for metastasis-directed therapies at progression. Local regional outcomes appear improved to historical data of cCRT alone.